Perancangan Creative and Performing Arts Center di Medan dengan Pendekatan Arsitektur Semiotik - Tarigan, Lihayati Rizka; Marisa, Amy (Dinasti Research, 2025)
The Creative and Performing Arts Center building that will be designed with a Semiotic Architecture approach aims to make the building better known by the presence of signs and symbols in the form of Malay ornaments on the exterior and interior of the building as a sign of the Creative and Performing Arts Center building located in Medan City. With the design method starting from the search for ideas or ideas, then looking for related problems along with solutions and objectives of the design. by using analysis techniques used include site analysis, function analysis, activity analysis, space analysis, form analysis, structural analysis, and utility analysis. The research results of the Semiotic Architecture Concept used in the building can function as a marker that there is a Creative and Performing Arts Center building in Medan with supporting facilities provided, namely in the form of galleries, cafes, restaurants, and shops supporting building functions which can keep a commercial building running when there is no performing arts activity.